Strategi Raya Sriwijaya dan Melaka - Wulandari, Prisca Kiki (Universitas Negeri Malang, 2020)
This study attempted to explore the political strategy of two Malay kingdoms, Srivijaya and Malacca, which was seen from the theory of grand strategy. The library research was used to address the main question of grand strategy from two kingdoms. Malacca seemed to continue how did Srivijaya manage the geopolitical balance in the Straits of Malacca. If Srivijaya sent their embassies to the major kingdoms in Asia, Malacca did the same. Malacca also negotiated the friendly relations to the Pasai and Ming Dynasty of Cina. Social life either during Srivijayan or Malaccan times depended on maritime activities. Both kingdoms initiated an alliance with the seafaring communities, seamen, and pirates, to decrease the trading risk and attracted the merchants to populate both port-cities. These historical patterns are not merely a public memory but an invaluable lesson for national defense for this country.